2017
DOI: 10.4103/1319-2442.220872
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic randomized controlled trial comparing pathway-based versus usual care in community-acquired acute kidney injury

Abstract: Clinical pathways have shown conflicting evidence in improvement of several patient-centered outcomes across different clinical settings. However, the effectiveness of clinical pathway in management of acute kidney injury (AKI) has not been reported. Therefore, we aimed to assess the length of hospital stay (LOS) and patient-centered outcomes in community acquired AKI and compared pathway care (PC) versus usual care (UC). The CHAMP-Path AKI Trial is a pragmatic, parallel, single-blind randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, the study method and collaboration of pharmacy with the multidisciplinary team were presented at other international research forums, such as The Principles and Practice of Clinical Research course in Sao Paulo, Brazil in 2011 offered by Harvard T H Chan School of Public Health and the Global Conference of the American College of Clinical Pharmacy, CA, United States in 2015. Finally, to date, two papers reporting CHAMP-Path studies were published with the coordinating clinical pharmacist as the leading author or co-author [ 22 , 23 ]. In the acute kidney injury study, the primary outcome of median length of stay (LOS) was 4.96 days (interquartile range of 6.57) for the pathway care compared to 4.8 days (interquartile range of 6.84 days) for the usual care ( p = 0.8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study method and collaboration of pharmacy with the multidisciplinary team were presented at other international research forums, such as The Principles and Practice of Clinical Research course in Sao Paulo, Brazil in 2011 offered by Harvard T H Chan School of Public Health and the Global Conference of the American College of Clinical Pharmacy, CA, United States in 2015. Finally, to date, two papers reporting CHAMP-Path studies were published with the coordinating clinical pharmacist as the leading author or co-author [ 22 , 23 ]. In the acute kidney injury study, the primary outcome of median length of stay (LOS) was 4.96 days (interquartile range of 6.57) for the pathway care compared to 4.8 days (interquartile range of 6.84 days) for the usual care ( p = 0.8).…”
Section: Resultsmentioning
confidence: 99%
“…In the acute kidney injury study, the primary outcome of median length of stay (LOS) was 4.96 days (interquartile range of 6.57) for the pathway care compared to 4.8 days (interquartile range of 6.84 days) for the usual care ( p = 0.8). Secondary outcomes of 30-day readmission and in-hospital mortality were also not statistically different [ 23 ]. Preliminary findings of unpublished data demonstrated that heart failure and venous thromboembolism showed a significant reduction in primary outcome of LOS and further data analysis for the findings of the studies is ongoing.…”
Section: Resultsmentioning
confidence: 99%